Efisiensi Energi Listrik Kampus Undip Tembalang - Karnoto, Karnoto (Transmisi, 2008)
Energy is one part of the important in everyday life. The energy consumption especially electrics energy have to pay attention requirement and economics level.  So that electrics energy used as according to requirement. Thereby consumption  energy pay attention energy efficiency. This research is to evaluate usage consumption energy of Diponegoro University Tembalang Campus ( Faculty MIPA and FPIK, FKM, and FPsychology). This Benefit Research is to give alternative  solution subscribe PLN electrics or merger. Result of Research yielded is forth of the faculty of customer based on energy capacities attached in the reality still not yet as according to usage. Given by solution is Customer FMIPA can be achieved by down grading its tarrif-class ( from 345 KVA to 197 KVA)  and FPIK, FKM and F Psychology (240 KVA to 131 KVA).  Other Alternative is Merger of  FPIK, FKM And F Psychology with F MIPA.Keywords: Energy, Consumption, Efficiency, Capacity